Kepatuhan Pajak: Persepsi Ilusi Menyaksikan Fenomena Keserakahan Pejabat Pajak Indonesia - Ellyn Citra Putrantri; Shara Merry Palupi (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This study aims to present a comprehensive portrait of the shift in perception, not only related to tax compliance from the taxpayer's perspective, but also as a turning point in taxpayer perceptions of institutions and officials within the Directorate General of Taxes, Ministry of Finance of the Republic of Indonesia. Furthermore, this study raises the issue of the illusion of compliance as a form of resistance by taxpayers who have lost trust in tax institutions and officials. This study was completed using a qualitative method approach. The results of this study illustrate that taxpayer perceptions of tax compliance and obedience are contradictory, in line with various cases of tax corruption in Indonesia. This study is expected to contribute as a reference material for the Indonesian government to reconstruct the level of public trust in the Directorate General of Taxes, Ministry of Finance of the Republic of Indonesia, as well as the tax management system in Indonesia, considering that taxes are the backbone of the Indonesian state.